Transformational Leadership Style of Principals in Primary Schools: Case Study in Sukalarang Sub-District, Sukabumi Regency - Mulfi Sandi Yuda; Ike Rachmawati; Sugihartto Sugihartto (International Journal of Economics (IJEC), 2023)
The purpose of this study aims to analyze the transformational leadership style applied by the Principal, in elementary schools in Sukalarang District, Sukabumi Regency, West Java. Leadership Style is focused on charismatic leadership, inspirational motivation, intellectual stimulation, and individual consideration. The data collection technique is carried out through observation, interviews, and documentation. The research location focused on Sukalarang District, Sukabumi Regency, West Java. The informants in this study were school principals, teachers, and education staff as many as 15 people. Data analysis is carried out by selecting answers obtained from informants and then collected for analysis and conclusions. The data analysis used is data triangulation. The results of the study were obtained, 1) charismatic leadership from the principal, namely every democratic decision-making with educators, and the principal as an actor in carrying out transformational leadership takes a deliberation approach (open management) to make a decision. 2) Inspirational motivation from the principal is shown by Building the will to achieve achievements and planting building a positive organizational culture and organizational climate without discrimination. 3) Intellectual stimulation including the principal creates a positive work culture by strengthening human relations between educators formed through teamwork skills, communication, and the same view on the vision and mission. 4) individual consideration, namely the principal's concern in developing the character and performance of educators through various pieces of training such as independent curriculum training, scientific papers, Teacher Professional Education, and independent teaching Platform (PMM), as well as the Principal gave appreciation to educators for their achievements.